Pengaruh Kemampuan Berpikir Kreatif, Berpikir Kritis dan Lingkungan Belajar Terhadap Hasil Belajar Ekonomi: The Effect of Creative Thinking, Critical Thinking, and Learning Environment on Learning Outcomes in Economics - Gustiara, Yora; Gumilar, Rendra; Sadiah, Ati (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study was motivated by the low learning outcomes of students in economics. The purpose of this study was to analyze the effect of creative thinking, critical thinking, and learning environment on student learning outcomes. The research method used was a survey with an associative research design. The research population consisted of 251 students in grade XI of SMA Negeri 2 Tasikmalaya City who took Economics, with a sample of 154 students selected using the simple random sampling technique. Data collection was carried out through questionnaires, and data analysis used multiple linear regression. The results showed that creative thinking skills, critical thinking skills, and the learning environment each had a positive and significant effect on student learning outcomes with a significance value of 0.000. In addition, simultaneously, the three variables also had a significant effect on student learning outcomes. These findings indicate that improving creative thinking skills, critical thinking skills, and a conducive learning environment can contribute to improving student learning outcomes in economics.